Supplementary data on metabolite differences between certain groups - Lind, Lars; Salihovic, Samira; Sundström, Johan; Elmståhl, Sölve; Hammar, Ulf; Dekkers, Koen; Ärnlöv, Johan (Uppsala University, 2021)
An overview of metabolite differences between certain groups; obese (OB) subjects without MetS vs normal-weight (NW) without MetS, overweight (OW) without MetS vs normal-weight (NW) without MetS, OB with vs OB without MetS, and to the right metabolites vs insulin resistance (Matsuda index). A positive beta denote that the metabolite is higher in obese subjects without MetS compared to normal-weight without MetS etc. Only metabolites with FDR<0.05 are shown. A p-value of 0 denotes that p<e-25.
The dataset was originally published in DiVA and moved to SND in 2024.

En översikt över skillnader i metabolism mellan vissa grupper. Se engelsk version för ytterligare beskrivning.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Supplementary data on metabolite differences between certain groups
Keywords: energy consumption (metabolism); energiförbrukning (ämnesomsättning); metabolism; ämnesomsättning; insulin resistance; insulin resistance; metabolic syndrome; metabolic syndrome; Epidemiology; Epidemiology; obesity; obesity; epidemiology; epidemiology; Medical Science; Medical Science; metabolomics; metabolomics; Endocrinology and Diabetes; Endokrinologi och diabetes